Cultural melancholy : readings of race, impossible mourning, and African American ritual - Singleton, Jermaine, 1974- (Urbana : University of Illinois Press, 2015)
"A daring cultural and literary studies investigation, Cultural Melancholy explores the legacy of unresolved grief produced by ongoing racial oppression and resistance in the United States. Using acute analysis of literature, drama, musical performance, and films, Singleton demonstrates how rituals of racialization and resistance transfer and transform melancholy discreetly across time, consolidating racial identities and communities along the way. He also argues that this form of impossible mourning binds racialized identities across time and social space by way of cultural resistance efforts. Singleton develops the concept of "cultural melancholy" as a response to scholarship that calls for the separation of critical race studies and psychoanalysis, excludes queer theoretical approaches from readings of African American literatures and cultures, and overlooks the status of racialized performance culture as a site of serious academic theorization. In doing so, he weaves critical race studies, psychoanalysis, queer theory, and performance studies into conversation to uncover a host of hidden dialogues--psychic and social, personal and political, individual and collective--for the purpose of promoting a culture of racial grieving, critical race consciousness, and collective agency. Wide-ranging and theoretically bold, Cultural Melancholy counteracts the racial legacy effects that plague our twenty-first century multiculture"--
"More than 130 years have passed since the ratification of the 13th Amendment and the U.S. Constitution declared slavery illegal, yet the nation still suffers from legacies of slavery. In this cultural and literary studies project, Singleton charts new territory in the relationship between critical race studies, psychoanalysis and performance studies to explore and address the psychic and social remains of the nation's history of slavery and discrimination in a post-racial moment. The book brings psychoanalytic paradigms of mourning and melancholia and discussions of race and performance into conversation with literary representations of America's post-Emancipation life and ritual practice to challenge scholarship that fails to engage with both ethnic studies and psychoanalysis to interpret history. The work further explores how theatrical and musical performance contribute to the construction and deconstruction of historical and subjective grief over U.S. racial legacies. Singleton develops a theory of cultural melancholy to provide a framework to engage a process that, through which modern ritual practices, constructs, maintains, and link normative and minority racial positions in relation to social loss and unresolved grief. The discussion of primary texts ranges from F. Scott Fitzgerald's The Great Gatsby to James Baldwin's Go Tell It on the Mountain to Billie Holiday's memoir, and in the process ranges different geographical, political, and historical senses. By analyzing African American and white subject-formations as represented in literature, drama, and musical performance in the twentieth century, the project helps us understand the process of coming to terms with historical traumas of slavery, segregation, and racial discrimination"--
Coda: On Conformity to the Category of Time (Race)Notes; Bibliography; Index.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: American literature -- African American authors -- History and criticism; Grief in literature; Mourning customs -- United States; African Americans -- Race identity -- History; Chagrin dans la littérature.; Deuil -- Coutumes -- États-Unis.; Noirs américains -- Identité ethnique -- Histoire; SOCIAL SCIENCE -- Ethnic Studies -- African American Studies; HISTORY -- Social History; LITERARY CRITICISM -- American -- General; African Americans -- Race identity; American literature -- African American authors; Grief in literature; Mourning customs; United States; American Literature; English; Languages & Literatures; Criticism, interpretation, etc; History